Prevalence and determinants of fetal macrosomia in Bangladesh - Islam, Md. Zahidul; Chowdhury, Mohammad Rocky Khan; Billah, Baki; Rashid, Mamunur; Kabir, Russell; Hasan, Mehedi; Kader, Manzur (Frontiers in Pediatrics, 2024)
Background Fetal macrosomia, marked by excessive birth weight, is a significant public health issue in developing countries, yet it has received less attention compared to low birth weight. This study aims to determine the prevalence of fetal macrosomia in Bangladesh and its associated factors. Methods The study utilized data from 4,754 women with complete birth weight information of their children from the Bangladesh Multiple Indicator Cluster Survey (MICS) −2019, defining fetal macrosomia as newborns with a birth weight ≥4,000 g regardless of gestational age. Bivariate logistic regression assessed associations between independent variables and fetal macrosomia, presenting adjusted odds ratios (AOR) and a 95% confidence interval (CI), while controlling for potential confounders such as women's age, wealth index, education, healthcare utilization, comorbidities, newborn sex, and place of residence. Results The prevalence of fetal macrosomia was 11.6%. Significant associations with fetal macrosomia included higher maternal age group (30–34 years) (AOR =<sans-serif> 1</sans-serif>.36, 95% CI = 1.07–1.74), secondary level of mother's education (AOR =<sans-serif> 1</sans-serif>.95, 95% CI = 1.43–2.66), experienced physical attacks (AOR =<sans-serif> 1</sans-serif>.41, 95% CI = 1.06–1.88), hypertension during pregnancy (AOR =<sans-serif> 1</sans-serif>.54, 95% CI = 1.15–2.07), and rural residence (AOR =<sans-serif> 1</sans-serif>.25, 95% CI = 1.15–1.49). Female infants had 18% lower odds of being macrosomic compared to male infants (AOR =<sans-serif> 0</sans-serif>.82, 95% CI = 0.72–0.93). Conclusion One in ten infants in Bangladesh are born with macrosomia, necessitating a multi-faceted approach involving improving maternal nutrition, promoting healthy lifestyles, enhancing access to quality prenatal care, and addressing socioeconomic, residential, and healthcare system challenges, underlining the importance of further community-based research to expand the study's scope.